Challenges and Required Competencies toward Effective Academic Leadership in Indonesian Theological Institution - Bakhoh Jatmiko; Sherly Ester Kawengian (Jurnal Teologi Berita Hidup, 2023)
Law No. 20 of 2003 concerning the National Education System is the ground of conveying a professional and accountable education model system in Indonesia. This also applies to higher theological education institutions (THEI) that want to get recognition and accreditation from the government. The obligation to comply with this regulation presents its own challenges for theological institutions which are generally established as one of the ministry training entities for the church. Therefore, this study was conducted to obtain information related to particular challenges and competencies of an academic leader in THEI in Indonesia. The study employs a qualitative, systematic grounded theory approach to explore leadership challenges and characteristics in Theological institutions. This study found that factors contributing to effective leadership in dealing with legal and accreditation issues are personal, managerial, practical, administrative, and relational skills. This finding shows that in general, leadership at THEI still needs strengthening in various areas.